Degradation, Meaning Shift, and Redefinition of the City Parks’ Social Function in the Presence of Virtual Space Facility - Handoyotomo Handoyotomo; Adiansya Halimawan; Nensi Golda Yuli (Departement of Architecture, Universitas Islam Indonesia, 2018)
As one of the big cities in Indonesia, Bandung has now made many improvements to the city park facilities and infrastructure. The quality improvement can be seen not only in the physical form of various city spaces but also though the free internet access available for park users. This has an impact on the behavior of park users, which slowly affects the dynamics of park activities as well, especially the emergence of virtual space. The presence of virtual space in the city park provides a variety of positive and negative responses in the way people socialize. This paper aims to examine the phenomenon and impacts, the meaning shift, and the redefinition the social functions of urban parks due to the availability of free internet facilities that give rise to virtual spaces in the parks of Bandung. The data were taken from the Superhero Park, Elderly Park, Fitness Park, and Dago Park using structured interviews and observations of visitor activities as the data collection techniques. It is found that the presence of wifi facilities is viewed positively in terms of information access, but is viewed negatively in regard to the essential functions of urban parks which are originally created as a social space. Therefore, the study concludes that there has been a degradation of functions in the urban park facilities, because the nature of virtual space itself tends to bring humans to get carried away in it and interrupt their activities from the space of reality. City parks have also experienced a shift in meaning, thus creating a build-up of space that creates virtual space into the real world in the form of a park.Keywords: City Parks, Virtual Spaces, Social, Bandung